Masa Pembaruan Pendidikan Islam di India - M.Ikhsan; Nazila Nasywa Maulida; Amrin Batua; Mahfud Ifendi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the period of Islamic education reform in India during the 19th to early 20th centuries, focusing on educational transformation, religious thought renewal, and socio-political impacts. Employing qualitative research with a library research approach, the study analyzes primary and secondary sources to gain comprehensive insights. The findings reveal that educational transformation, through integrating modern curricula with Islamic values and revitalizing traditional madrasahs, played a pivotal role in addressing the challenges of modernity. Religious thought reform, via ijtihad and reinterpretation of religious texts, facilitated a dialogue between Islamic traditions and modernity. The socio-political impacts included the emergence of an educated Muslim middle class, women's empowerment, and increased political engagement of the Muslim community. This research concludes that this historical experience provides valuable lessons for contemporary Islamic reform efforts, particularly in harmonizing Islamic values with modern demands.